Framework to Humanise Research Support in Academic Institutions - Ishak, Nor Azira; Maniam, Nengaswary; Ramachandran, Jayalaskhmy; Sharidan, Sharina; Ab Rahman, Nurul Huda (Journal of Research Management and Governance, 2024)
Purpose The purpose of the study is to identify the attributes to build a successful research management ecosystem, to understand the extent to which identified attributes contribute to successful research support environment, and to develop a framework for strong research management in Higher Education Institutions (HEIs). Methodology This study used a mixed-method approach. Through recorded discussion with academics and non-academics involved in research and research support, we identified the areas to be addressed for an efficient research experience. We then conducted a pilot study with 50 participants to validate the findings from the qualitative analysis. Findings We found that a research management ecosystem system requires ethical conduct from individuals and an ethical culture which is grounded on honourable behaviour of all organisational participants. This is not only aligned to Malaysian codes of responsible conduct in research but is also in accordance with existing guidelines. A new framework is suggested in this paper based on which, universities can create a research ecosystem that balances global goals with local relevance, resulting in a collaborative working model that is more strategic.